Feeding behaviour, intake, apparent digestibility and plasma metabolites of Latxa dairy ewes as affected by cold-pressed oilseed cakes and sainfoin - García-Rodríguez A.; Goiri I.; Pineda-Quiroga C.; Pascual A.; Atxaerandio R.; Ruiz R. (Innovation for sustainability in sheep and goats, 2019)
The hypothesis tested was that the tanniferous forage sainfoin, given as hay, has an advantage over a typical fescue in dairy ewes with respect to intake, ruminal fermentation and ingestive behaviour when cold pressed oilseed cakes rich in crude fat are formulated in the concentrate. A lactation trial was carried out with 72 blackfaced Latxa dairy ewes at early lactation in a 2 x 3 factorial arrangement involving two forages (fescue and sainfoin hay) and 3 experimental concentrates. Concentrates were formulated to contain coldpressed rapeseed cake, cold-preseed sunflower cake or palm as fat sources and to provide equal amounts of crude protein fat and energy. No interactions between concentrate and forage were observed. None of the measured traits was affected by concentrate. However, feeding sainfoin increased forage eating time (356 vs. 279 min/d, P<0.001), reduced rumination time (325 vs. 422 min/d, P<0.001), increased forage dry matter intake (1.84 vs. 0.99 kg/d, P<0.001), apparent organic matter digestibility (613 vs. 580 g/kg, P = 0.011) and IGF-1 plasma concentration (110.7 vs. 98.6 ng/ml, P = 0.014). In conclusion, cold pressed oilseed cakes can be used as feedstuffs regardless of the forage used.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)